Pengaruh disiplin kerja terhadap kinerja karyawan pada PT. Daeah E&C RDMP Balikpapan - Pratama, Ricky Renaldy; Hadiyanti, Sofia Ulfa Eka; Askiah (International Journal Administration, Business & Organization, 2025)
This study aims to determine the effect of work discipline on employee performance at PT Daeah E&C RDMP Balikpapan. Work discipline is an important factor in creating a productive and efficient work culture, and has a direct impact on individual performance within an organization. This study employs a quantitative approach using descriptive methods and simple linear regression analysis. The study population consists of all 40 employees at PT Daeah E&C RDMP Balikpapan, all of whom were selected as samples using total sampling techniques. Data collection was conducted through the distribution of questionnaires and analyzed using SPSS software. The results of the study indicate that work discipline has a positive and significant impact on employee performance. The higher the level of work discipline, the better the performance demonstrated. In practice, it is important for companies to continuously improve discipline through consistent regulations, training, and supervision to support work productivity. From a theoretical perspective, this study reinforces organizational behavior theory, which states that internal factors such as discipline significantly contribute to performance. Therefore, companies need to maintain and improve work discipline to support optimal work productivity. These findings provide empirical contributions to the development of human resource management studies in strategic industrial project environments.